Molybdenum and Niobium Codoped B-Site-Ordered Double Perovskite Catalyst for Efficient Oxygen Evolution Reaction - Sun, Hongqi; Chen, G.; Sunarso, J.; Dai, J.; Zhou, W.; Shao, Zongping (American Chemical Society, 2018)
An abundant, highly active, and durable oxygen evolution reaction (OER) electrocatalyst is an enabling component for a more sustainable energy future. We report, herein, a molybdenum and niobium codoped B-site-ordered double perovskite oxide with a compositional formula of Ba2CoMo0.5Nb0.5O6-d(BCMN) as an active and robust catalyst for OER in an alkaline electrolyte. BCMN displayed a low overpotential of 445 mA at a current density of 10 mA cm-2disk. BCMN also showed long-term stability in an alkaline medium. This work hints toward the possibility of combining a codoping approach with double perovskite structure formation to achieve significant enhancement in the OER performance.